Possible role of endocannabinoids in olfactory and taste dysfunctions in Alzheimer’s and Parkinson’s patients and volumetric changes in the brain - Petekkaya, Emine; Kus, Berna; Dogan, Serdar; Bayarogullari, Hanifi; Mutlu, Turay; Melek, Ismet Murat; Arpaci, Abdullah (Elsevier BV, 2022)
The purpose of this study is to determine the volumes of primary brain regions associated with smell and taste in Alzheimer's and Parkinson's patients and healthy controls using MR imaging and examine volumetric changes in comparison to smell/taste questionnaire and test results and endocannabinoid (EC) levels. The study included 15 AD patients with mild cognitive dysfunction scored as 18 ≤ MMSE ≤ 23, 15 PD patients with scores of 18 < MoCA < 26 and 18 ≤ MMSE ≤ 23, and 15 healthy controls. A taste and smell questionnaire was given to the participants, and their taste and smell statuses were examined using the Sniffin' Sticks smell identification test and Burghart Taste Strips. EC levels were analyzed in the blood serum samples of the participants using the ELISA method. The volumes of the left olfactory bulb (p = 0.001), left amygdala (p = 0.004), left hippocampus (p = 0.008), and bilateral insula (left p = 0.000, right p = 0.000) were significantly smaller in the Alzheimer's patients than the healthy controls. The volumes of the left olfactory bulb (p = 0.001) and left hippocampus (p = 0.009) were significantly smaller in the Parkinson's patients than the healthy controls. A significant correlation was determined between volume reduction in the left Rolandic operculum cortical region and taste dysfunction. EC levels were significantly higher in both AD (p = 0.000) and PD (p = 0.006) in comparison to the controls. Our results showed that volumetric changes occur in the brain regions associated with smell and taste in Alzheimer's and Parkinson's patients. It was observed that ECs played a role in these volumetric changes and the olfactory and taste dysfunctions of the patients.
Keywords: Parkinson Disease; Sniffin' Sticks test; Burghart taste strips; Neurodegenerative disease; Olfactory Bulb; Olfactory/taste dysfunction; Parkinson disease; Smell; Olfaction Disorders; Taste Disorders; Alzheimer Disease; Taste; Humans; Alzheimer disease; Endocannabinoid; Endocannabinoids